PENGARUH BRAND IMAGE, KUALITAS PRODUK, REFERENCE GROUP, DAN IKLAN TERHADAP MINAT BELI GARNIER MEN - Oktaviami SE (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to identify the influence of brand image, product quality, reference group, and advertisement on the purchase intention toward male cosmetics products ('Garnier Men') and to determine the variable that dominantly affects the purchase intention toward 'Garnier Men' in Kediri. This explanatory research uses quantitative approach and survey method. Using nonprobability sampling method with purposive sampling technique, 140 people of Kediri who had never bought 'Garnier Men' but had some knowledge about product from other people were selected as the respondents. The data were processed trough multiple linear regression analysis with consideration the classical assumption test. The result of research indicates that brand image, product quality, reference group, and advertisement have significant effect on the purchase intention toward Garnier Men, where brand image has the dominant influence.Keywords: brand image, product quality, reference group, advertisement, purchase intention